Tumour immune microenvironment in primary and metastatic papillary renal cell carcinoma. Issue 3 (11th December 2019) - Eich, Marie‐Lisa; Chaux, Alcides; Mendoza Rodriguez, Maria Angélica; Guner, Gunes; Taheri, Diana; Rodriguez Pena, Maria Del Carmen; Sharma, Rajni; Allaf, Mohamad E; Netto, George J
Abstract : Aims: Among renal cell carcinoma (RCC) the tumour immune microenvironment has been best characterised in clear cell RCC. In this study we investigated the expression of several immune markers, including PD‐L1, FoxP3 and CD8 in primary and metastatic papillary RCC. Methods and results: Three tissue microarrays were constructed from 78 cases with primary papillary RCC and paired metastatic tumour (24 cases) from 78 patients treated between 1982 and 2014. Immunohistochemistry analysis was performed using commercially available antibodies for PD‐L1 (clone E1L3N), FoxP3, CD8 and Ki‐67. Markers expression level in tumour and/or associated immune cells was analysed by tissue type (non‐tumour versus primary tumour versus metastatic tumour) and correlated to clinicopathological features and outcome. Conclusion: We found PD‐L1 expression in up to one‐quarter of primary and metastatic papillary RCC. On univariate analysis, CD8/FoxP3 ratio >1 was associated with favourable outcome, whereas papillary RCCs with high numbers of dual CD8/Ki‐67‐positive lymphocytes showed an increased likelihood for tumour progression and overall and cancer‐related mortality. The association of CD8/FoxP3 ratio >1 and high count of CD8/Ki‐67 with outcome remained significant on multivariate analysis when adjusting for stage, grade and patient's age.